The Covid-19-Pandemic and Economic Crises: a multiple burden for women in private households - Wöhl, Stefanie; Lichtenberger, Hanna (Momentum Quarterly, 2021)
The article discusses how unpaid social reproduction is related to paid (care) work since the latest financial and economic crisis 2008 and within the ongoing Covid-19 pandemic. We discuss this in the context of austerity measures implemented in Spain, because they show particularly well how the effects of austerity policies have an impact on the social and health system, and how women are significantly more affected by unpaid social reproductive work during the Covid-19 pandemic in a more detailed case study on Austria.